Raúl Benítez Zenteno y José B. Morelos (comps.). Grandes problemas de la ciudad de México. México : DDF : IPN : Plaza y Valdés, 1988 - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1989)
RAÚL BENÍTEZ ZENTENO y JOSÉ B. MORELOS (comps.), Grandes problemas de la ciudad de México, DDF, IPN Y Plaza y Valdés, México, 1988.